Pemanfaatan Sistem Keputusan Dalam Mengevaluasi Penentuan Aplikasi Chatting Terbaik Dengan Multi Factor Evaluation Process - Indra Riyana Rahadjeng; Muhammad Noor Hasan Siregar; Agus Perdana Windarto (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
The rapid development of chat application features shows that information technology is increasingly global. This study aims to help smartphone users, especially beginners, to be more selective in choosing the chat application that suits their needs. The method used in this study is a Decision Support System with a Multi-Factor Evaluation Process (MFEP) as a solution for solving cases. The dataset used in this study was obtained by distributing questionnaires to respondents at random, both directly and virtually by using the google form to provide an assessment of the questionnaire to some active users of the Chat application. The alternatives used are Messager, Line, Instagram, Whatsapp, and Telegram and the criteria used are storage media, security, display (interface), application features, and network usage. The results obtained indicate that the Whatsapp alternative is the first recommendation as to the best chat application with a final score of 8.l5. Alternative Instagram became the second recommendation with a final score of 7.21 and Messager became the third recommendation with a final score of 6.18.